Integration of pheromones and the entomopathogenic fungus for the management of the banana weevil - Tinzaara, William; Gold, Cliford S.; Nankinga, C.; Dicke, M.; Huis, A. van; Ragama, P.E.; Kagezi, G.H. (2004)
Candidate strains of the fungus Beauveria bassiana have been identified for the intergrated pest management of the banana weevil (Cosmopolites sordidus). However, the important limiting factor has been the lack of an economic and effective delivery system to maximize field effects. Catches in pheromone traps are low and currently, costs of using B. bassiana are high. The two methods of pheromone trapping and application of fungus, may be intergreted to provide a cost effective strategy for the control of the pest. We conducted studies to determine the potential for the pheromone-baited traps to aggregate the banana weevil around the trap mat and to determine the effect of different delivery systems of B. bassiana using pheromones. Our data show that twice as many weevils were captured in pseudostem traps at the base of the trap mat (pheromone-baited mat) than at mats< 5m from the trap mat, and four times as many than at mats > 5m away. The results suggest that many weevils are attracted to pheromone lures but fail to enter the traps, resulting in weevil aggregation in the vicinity of pheromone traps.